2009
DOI: 10.1007/s00330-009-1619-8
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MR imaging of kidneys in patients with chronic kidney disease: initial study

Abstract: Diffusion-weighted MR imaging is feasible in the assessment of renal function, especially in the detection of early stage renal failure of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
82
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 16 publications
9
82
1
Order By: Relevance
“…Quantitative diffusion-weighted magnetic resonance imaging (MRI) may offer this opportunity and can play a role in the evaluation of renal disease. Several studies have indicated the potential use of the apparent diffusion coefficient (ADC) as a marker of renal function, showing lower renal ADC in kidney dysfunction (4)(5)(6)(7)(8)(9). Yet, there are only a few studies concerning the use of renal quantitative diffusion-weighted imaging (DWI) in diabetic nephropathy (5, 9-11).…”
mentioning
confidence: 99%
“…Quantitative diffusion-weighted magnetic resonance imaging (MRI) may offer this opportunity and can play a role in the evaluation of renal disease. Several studies have indicated the potential use of the apparent diffusion coefficient (ADC) as a marker of renal function, showing lower renal ADC in kidney dysfunction (4)(5)(6)(7)(8)(9). Yet, there are only a few studies concerning the use of renal quantitative diffusion-weighted imaging (DWI) in diabetic nephropathy (5, 9-11).…”
mentioning
confidence: 99%
“…Moreover, the water diffusion between intra and extra-cellular can be estimated by the apparent diffusion coefficient (ADC) (11). In renal parenchyma, the value of ADC mainly depends on the intra-and extra-cellular components fraction, ambient temperature, membrane permeability and capillary perfusion (12)(13)(14). Thus, DW-MRI can quantify alterations in water content as well as water exchange rate between intra and extra-cellular aspects of the kidney.…”
mentioning
confidence: 99%
“…Considerable attention has been made to investigate the renal DWI across the world (4-6), and some recent studies had demonstrated that the DWI has potential clinical value in evaluating some renal diseases (7-10), such as renal artery stenosis, diffuse renal disease, renal tumor and renal infection (11)(12)(13)(14)(15), etc. However, as a novel functional imaging for the investigation of renal function, the DWI is mainly applied in adult patients and the studies focusing on renal diffusion of infants is scarce, and no study at present was found with regard to using renal ADC values to explore the hydronephrotic kidney in single children population.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it would be difficult to exactly differentiate renal cortex and medulla in that situation and the measurement error will certainly increase when the ROIs are placed onto the cortex and medulla respectively. In addition, Xu et al (11) reported no significant signal difference was found between the renal cortex and medulla in DWI. Therefore, the approach of placing the ROI on specific plane was adopted in this study to measure the ADCs of local renal parenchyma.…”
Section: The Change Pattern Of Adc Values In Hydronephrotic Kidneys Amentioning
confidence: 95%